2008
DOI: 10.3201/eid1404.071083
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Population of Flucytosine-ResistantCandida tropicalisfrom Blood Cultures, Paris, France

Abstract: Candida tropicalis is a diploid ascomycetes yeast responsible for 4%-24% of candidemia. Resistance to fl ucytosine is rarely described for this species but was observed for 45 (35%) of 130 C. tropicalis isolates recovered from blood cultures in the Paris area in a 4-year survey. The aims of this study were to test the hypothesis that the fl ucytosine-resistant isolates could represent a subgroup and to determine the relationship between epidemiologic and genomic data. Epidemiologic data and gene sequences were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
39
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 22 publications
2
39
1
Order By: Relevance
“…For other clinically important yeasts, e.g., C. albicans and C. tropicalis, resistances to flucytosine were also described in the literature (17,21). These resistances are determined not only genetically; they also cause differences in phenotypical and epidemiological characteristics of susceptible and nonsusceptible yeast populations, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For other clinically important yeasts, e.g., C. albicans and C. tropicalis, resistances to flucytosine were also described in the literature (17,21). These resistances are determined not only genetically; they also cause differences in phenotypical and epidemiological characteristics of susceptible and nonsusceptible yeast populations, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These resistances are determined not only genetically; they also cause differences in phenotypical and epidemiological characteristics of susceptible and nonsusceptible yeast populations, respectively. Desnos-Ollivier et al (17) have shown that a flucytosinenonsusceptible C. tropicalis subgroup isolated from blood cultures has a higher incidence in patients with malignancies and is associated with lower mortality related to the infection. Currently, flucytosine has only a marginal therapeutic impact; however, the identification of the resistance is important for differentiation of Candida species, as demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A matched case-control study was nested within the YEASTS program, an active surveillance program on yeast BSI implemented in the Paris area in France (5). The study population included patients Ͼ17 years of age suffering from hematological diseases and Candida BSI between 1 October 2002 and 1 February 2010.…”
Section: -850)mentioning
confidence: 99%
“…FCY2, encoding a purine-cytosine permease, is involved in the uptake of 5FC, and URA3, encoding an orotidine 5Ј-phosphate decarboxylase, is involved in the metabolic pathway of uridylmonophosphate (UMP) in nucleic acid synthesis. Mutations on FCY1, FCY2, FUR1, or URA3 can result in 5FC resistance in certain yeast species (5,14,16,18,23,27,33). Interestingly, 5FC-resistant clinical isolates have been reported to be genetically related (6,14).…”
mentioning
confidence: 99%